Product Lifecycle Management (Volume 4): The Case Studies - Stark, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents some twenty case studies, showing how companies in different industry sectors and of different sizes make advances in Product Lifecycle Management (PLM). Like the author's previous volumes, this book provides a valuable resource for those wishing to learn about PLM and how to implement and apply it in their companies. Helping readers to · learn about implementing and benefiting from PLM; · learn about good PLM solutions and best practice; · improve their planning and decision-making abilities; · benefit from the lessons learned by the companies featured in the case studies; · proceed faster and further with PLM the book presents effective PLM solutions and best practices. At the same time, the case studies included demonstrate how different companies implement and benefit from PLM. Each case study is addressed in a separate chapter and details a different situation, enabling readers to put themselves in the situation and think through different actions and decisions. A valuable resource for PLM team managers and employees in engineering and manufacturing companies, the book is also of interest to researchers and students in industrial engineering fields. Chapter "PLM at PSA GROUPE" of this book is available open access under a CC BY 4.0 license. .
Introduction -- Case Study 1 -- Case Study 2 -- Case Study 3 -- Case Study 4 -- Case Study 5 -- Case Study 6 -- Case Study 7 -- Case Study 8 -- Case Study 9 -- Case Study 10 -- Case Study 11 -- Case Study 12 -- Case Study 13 -- Case Study 14 -- Case Study 15 -- Case Study 16 -- Case Study 17 -- Case Study 18 -- Case Study 19 -- Case Study 20 -- Summary. .
Keywords: Industrial Management; Project management; Engineering design; Operations research; Technological innovations; Strategic planning; Leadership; Industrial Management; Project Management; Engineering Design; Operations Research and Decision Theory; Innovation and Technology Management; Business Strategy and Leadership